Wie viel Reflexion braucht der Fremdsprachenlerner? - Myczko, Kazimiera (Glottodidactica, 2015)
This paper attempts to answer the question about the scope of reflection in foreign language teaching. The starting point is the assumption that through reflection on language and its use one can support language learning processes. The above considerations apply to the learner's perspective and they relate to process of fostering the development of language awareness and cultural awareness. Additionally, the article contains a list of instruments whose function is to facilitate student reflection in the process of developing learning awareness. At the end selected factors determining the scope of reflection in learning a foreign language are indicated.